Windows Server 2012 Automation with PowerShell Cookbook : over 110 recipes to automate Windows Server administrative tasks by using PowerShell - Goad, Ed (Quick answers to common problems., 2013)
Cookbook with recipes based on real life examples. This book is written to assist the daily tasks for systems administrators, engineers, and architects working with Windows Server 2012.